Current and Voltage Imbalances at BPTIK Universitas PGRI Semarang - Margono, Margono; Amiruddin, Muhammad; Farikhah, Irna (Advance Sustainable Science, Engineering and Technology, 2021)
Energy conservation is an effort to increase energy efficiency. This research conducted an energy audit in the BPTIK (Badan Pengembangan Teknologi Informasi dan Komunikasi) department room at the Universitas PGRI Semarang, observing the value of electrical parameters, especially unbalanced voltage and current that have the potential to cause neutral currents. In this study the calculated unbalanced voltage value is 0.64% and unbalanced current is 20.25%. From the current development, the neutral current produces an average of 1.72 Amperes. From the value of the neutral current can be calculated the energy lost in the conductor neutral wire per day is about 0.01% of energy consumption by the load per day